Effect of specific physiotherapy interventions in comparison with multisensory stimulation on neurobehavioral outcome and weight gain in preterm infants: a randomized control trial - Nadar, Unis D.; Thakkar, Pareshkumar A.; Shah, Chaitali (International Journal of Contemporary Pediatrics, 2017)
Background: A premature infant is deprived of in-utero sensory experiences which are essential for normal brain development and rather is exposed to unusual sensory stimuli in the Neonatal Intensive Care Units (NICU) that pose risk to the developing brain in terms of adverse neurodevelopmental outcomes. The objective of this study was to study and compare the effect of specific physiotherapy intervention with multisensory stimulation on neurobehavioral outcome and weight gain in preterm infants. Inclusion criteria was preterm infants appropriate for gestational age more than 32 weeks, babies who were hemodynamically stable and babies receiving full enteral feeds. Exclusion criteria were major congenital anomalies, inability to undergo intervention (any fracture) or perinatal asphyxia. Methods: Eligible infants were randomly allocated into one of the two groups. Group A was offered multisensory stimulation: Auditory, Tactile, Visual and Vestibular (ATVV). Group B received Specific Physiotherapy Intervention (SPI) in form of kinesthetic exercises, oil massage and oral stimulation. The outcome was studied before and after intervention. Appropriate statistical tests were applied. Results: Both the groups had better suck co-ordination and improvement on neurobehavioral scale following intervention when compared to pre-intervention status (P<0.0001). When both groups were compared, SPI group had better sucking coordination than ATVV group, improvement in neurobehavioral scale was similar in either group. Conclusions: In preterm infants, Specific Physiotherapy Interventions are more effective in improving suck co-ordination, has better weight gain and are equally effective in improving neurobehavioral outcome compared to multisensory stimulation.